(untitled) (Confluenţe Bibliologice, 2021)
Because it is summer time, it was natural for O.N.T. magazine, from July 1938, to dedicate this number to holidays on the Black Sea coast. It is selected interesting information about our sea with its rich beaches. It is the region of the Romanian maritime seaside resorts, considered as one of the most picturesque and comprehensive: Ekrene beach, Balchik, which tends to become a port, The Memory of Queen Maria, which is linked to the resort of Balchik, Mamaia, Constanta, Budachi resort, Cordon, Cosa, Poiana Țapului, in the field of tourism and nautical sports are proposed, Climate Resort in CampulungMoldovenesc.